FGM-based remote intervention for adults with type 1 diabetes: The FRIEND randomized clinical trial - Lee, Jinju; Lee, Myeong Hoon; Park, Jiyun; Kim, Kyung-Soo; Kim, Soo-Kyung; Cho, Yong-Wook; Han, Hyun Wook; Song, Young Shin (Frontiers in Endocrinology, 2022)
Background The use of flash glucose monitoring (FGM) in conjunction with proper education has been reported to improve glycemic control in people with diabetes on insulin therapy. However, there are still few randomized controlled trials on the educational effect, and an ideal educational model has not been established. This study aimed to estimate the efficacy of remote intervention for glycemic control in adults with type 1 diabetes using FGM. Methods In this single-center, randomized controlled trial, we enrolled adults with type 1 diabetes (HbA1c ≥7.0%). The participants were randomly assigned (1:1) to either FGM use with remote intervention (intervention group) or FGM use only (control group). Changes in glycemic outcomes such as HbA1c levels and continuous glucose monitoring metrics were evaluated at 12 weeks. Results Among 36 randomized participants (mean age, 44.3 years; mean baseline HbA1c, 8.9%), 34 completed the study. The remote intervention did not significantly reduce HbA1c levels. FGM use significantly improved HbA1c levels by −1.4% and −0.8% in both groups with and without remote intervention, respectively (P=0.003 and P=0.004, respectively). However, the intervention group showed significant increases in time with glucose in the range of 70–180 mg/dL (TIR; from 49.8% to 60.9%, P=0.001) and significant decreases in time with hyperglycemia (P=0.002) and mean glucose (P=0.017), but the control group did not. Moreover, the TIR (P=0.019), time with hyperglycemia >250 mg/dL (P=0.019), and coefficient of variation (P=0.018) were significantly improved in the intervention group compared to the control group. In particular, the CGM metrics improved gradually as the remote intervention was repeated. Furthermore, the intervention group reported higher treatment satisfaction (P=0.016). Conclusions Ongoing, personalized education during FGM use may lead to amelioration of glycemic control in adults with type 1 diabetes, even remotely. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT04936633, identifier NCT04936633.